Experimental evaluation of a single geogrid-reinforced stone column under varying surrounding soil conditions: Effects on bearing capacity and elastic modulus - Nguyen Thai, Linh; Nguyen Hai, Ha; Nguyen Duc, Manh; Prakash, Indra; Vu Anh, Tuan (Vietnam Journal of Earth Sciences, 2025)
This experimental study evaluates the influence of soil consistency on the ultimate bearing capacity and elastic modulus of single geogrid-reinforced and unreinforced stone columns installed in soft-to-very soft clay. Laboratory model tests were conducted in the Ho Thuong Tin area of Hanoi, Vietnam, under three controlled soil conditions with liquidity indices (IL) of 0.78, 1.0, and 1.5. A total of six displacement-controlled load tests were performed in a unit-cell setup, with and without a geogrid reinforcement layer at the column head. Results show that the inclusion of geogrid significantly enhanced both the ultimate bearing capacity and stiffness of the stone column: the bearing capacity increased by approximately 12–25%, and the elastic modulus (E₅₀) increased by 19–27% relative to unreinforced columns. The study indicates that geogrid reinforcement at the column head provides a technically material-saving and straightforward alternative to complete encasement, with potential economic advantages particularly for soft clays where lateral confinement is limited. The findings provide new experimental data to inform the design of geogrid-reinforced stone columns under varying soil conditions.